2016
DOI: 10.1038/srep38872
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a genome-wide association study implied that SHTIN1 may involve in the pathogenesis of NSCL/P in Chinese population

Abstract: Orofacial clefts are among the most common birth defects in humans worldwide. A large-scale, genome-wide association study (GWAS) in the Chinese population recently identified several genetic risk variants for nonsyndromic cleft lip with or without cleft palate (NSCL/P). We selected 16 significant SNPs from the GWAS I stage (P < 1.00E-5) that had not been replicated to validate their association with NSCL/P in 1931 NSCL/P cases and 2258 controls. Ultimately, we identified a NSCL/P susceptibility loci (rs170956… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…VAX1 knock-out mice have been shown to develop cleft palate, suggesting VAX1 has a potentially important role in nsCL/P etiology [4]. SHTN1 , sometimes known as KIAA1598 , codes for the protein shootin1 that is involved in neuronal polarization [50] and has also been reported to be relevant to the etiology of nsCL/P in several studies [9,51,52]. It is difficult to distinguish the more significant locus between the VAX1 and SHTN1 genes because of their close proximity and similar expression profiles in mice [9,47,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…VAX1 knock-out mice have been shown to develop cleft palate, suggesting VAX1 has a potentially important role in nsCL/P etiology [4]. SHTN1 , sometimes known as KIAA1598 , codes for the protein shootin1 that is involved in neuronal polarization [50] and has also been reported to be relevant to the etiology of nsCL/P in several studies [9,51,52]. It is difficult to distinguish the more significant locus between the VAX1 and SHTN1 genes because of their close proximity and similar expression profiles in mice [9,47,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, two of the lead SNPs were mapped to SHTN1. There were three SNPs at SHTN1 reported by previous GWASs: g.117068049G>A (rs7078160; Ludwig et al, 2012;Mangold et al, 2010;Sun et al, 2015), g.117086783C>G (rs10886040; Leslie et al, 2017), and g.117101266G>T (rs17095681; Wang et al, 2016). Most researchers believed that the risk gene was the adjacent gene VAX1, not SHTN1, because the SNP of SHTN1 is located downstream of VAX1 and the homozygous mutations of VAX1 led to mouse craniofacial malformations, including a cleft palate (Hallonet, Hollemann, Pieler, & Gruss, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies were conducted to investigate the genetic variants associated with NSCL/P risk. Several large‐scale genome‐wide association studies (GWASs) or related meta‐analyses in different populations identified some underlying risk genes (Beaty et al, ; Birnbaum et al, ; Grant et al, ; Leslie et al, ; Leslie et al, ; Ludwig et al, ; Ludwig et al, ; Mangold et al, ; Sun et al, ; Wang et al, ; Yu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…VAX1 knock-out mice have been shown to develop cleft palate, suggesting VAX1 has a potentially important role in nsCL/P aetiology 4 . SHTN1 , sometimes known as KIAA1598 , codes for the protein shootin1 that is involved in neuronal polarization 48 and has also been reported to be relevant to the aetiology of nsCL/P in several studies 8 49 50 . It is difficult to distinguish the more significant locus between the VAX1 and SHTN1 genes because of their close proximity and similar expression profiles in mice and it is unclear which is the functional gene in the area 8 45 50 51 .…”
Section: Discussionmentioning
confidence: 99%